Impact of Education on the Decision-Making and Economic Activity of Women in Lampung Province (Period 2019–2023) - Puput Melati; Ida Budiarty (International Journal of Economics and Management Sciences, 2025)
This study investigates the impact of education on the economic empowerment of women in Lampung Province during the 2019 to 2023 period. Despite advancements in educational access, significant gender disparities persist in Indonesia, particularly in Lampung, affecting women's participation in the workforce and political decision-making and contributing to wage gaps. This research aims to analyze how different levels of education influence women's political participation, their involvement in the labor force, and the proportion of their wages relative to men. Employing a quantitative descriptive approach with panel data regression analysis, the study utilizes secondary data from the Central Statistics Agency (BPS) and the National Labor Force Survey (SAKERNAS) across 15 regencies/cities in Lampung. Key findings reveal that while higher education (university level) significantly boosts women's labor force participation and wage proportion, secondary education (SMA) plays a more dominant role in fostering political engagement. Furthermore, the study confirms a persistent gender wage gap, with men's participation having a larger impact on wage proportion. These results underscore the critical role of education in women's empowerment and advocate for targeted policies to enhance educational access, promote equitable wages, and address systemic discrimination to achieve sustainable gender equality in Lampung